Stabilitas Ekstrak Antosianin Beras Ketan (Oryza sativa var. glutinosa) Hitam selama Proses Pemanasan dan Penyimpanan - Nanik Suhartatik; Merkuria Karyantina; Akhmad Mustofa; Muhammad Nur Cahyanto; Sri Raharjo; Endang Sutriswati Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
anthocyanin pigments are responsible for the red, blue, and purple colour in crop produces such as fruits, vegetables, rice, and flowers. This bioactive compound has been developed for natural colorants in food products, especially functional foods. The aims of this research were to study the stability of anthocyanin and its colour during heating in various temperatures and during storage under different conditions. The results showed that the higher the heating temperature and the longer the heating time, the higher degradation of anthocyanin. Except for anthocyanin extract heated below 50 c for not more than 15 min, it has increased the anthocyanin stability. antioxidant activities (% RSa, radical scavenging activity and fRaP value, Ferrous Radical Activity Power) decreased after the extract were heated at 70c. Extracts stored at room temperature with neutral solution (pH 7.0) have decreased their level of anthocyanin from 25 to 1.87 mg/100 mL. Storage at low temperature had not reduced significantly their anthocyanin concentration. ABSTRAKAntosianin sebagai senyawa yang menyebabkan timbulnya warna merah, biru, dan ungu pada padi, buah, sayuran, dan produk hortikultura lainnya, sangat berpotensi untuk dikembangkan sebagai bahan pewarna alami pada produk pangan fungsional. Tujuan dari penelitian ini adalah untuk mempelajari stabilitas dan warna ekstrak antosianin dari beras ketan hitam selama proses pemanasan dan penyimpanan. Hasil menunjukkan bahwa semakin tinggi suhu pemanasan dan semakin lama waktu pemanasan, menyebabkan kerusakan antosianin semakin banyak. Kecuali pada pemanasan <50 c tidak lebih dari 15 menit yang dapat meningkatkan kestabilan antosianin. aktivitas antioksidan (% RSa, radical scavenging activity dan nilai fRaP, Ferrous radical Activity Power) mengalami penurunan setelah dipanaskan pada suhu 70 oc. Penyimpanan pada suhu kamar dan pH 7,0 dapat menurunkan kadar antosianin ekstrak dari 25 menjadi 1,87 mg/100 mL. Sedangkan penyimpanan pada suhu rendah tidak menyebabkan perubahan kadar antosianin yang berarti.